2002
DOI: 10.1097/00008469-200212000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of digestive cancers and occupational exposure to asbestos

Abstract: While the role of exposure to asbestos in the development of several cancers such as mesotheliomas and bronchopulmonary cancers is now well established, the possible relationship between digestive cancers, other than peritoneal mesotheliomas, and occupational exposure to asbestos is still controversial. The great majority of the studies are based on mortality data. The aim of the study was to analyse the relationship between digestive cancer incidence and occupational exposure to asbestos in a population of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…An exposure-response trend for GI cancer was clear, especially after age and smoking were adjusted for, with an 8-fold risk in the highest exposure. There was generally limited evidence for the association of asbestos exposure with GI cancers; and existing studies reported inconsistent results in previous studies [11], [12], [39]–[41]. In the Quebec miners, a substantial excess mortality from gastrointestinal cancers was reported, though the authors suggested that some other factors, such as environments, perhaps selective, might also operate [35].…”
Section: Discussionmentioning
confidence: 99%
“…An exposure-response trend for GI cancer was clear, especially after age and smoking were adjusted for, with an 8-fold risk in the highest exposure. There was generally limited evidence for the association of asbestos exposure with GI cancers; and existing studies reported inconsistent results in previous studies [11], [12], [39]–[41]. In the Quebec miners, a substantial excess mortality from gastrointestinal cancers was reported, though the authors suggested that some other factors, such as environments, perhaps selective, might also operate [35].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there were no consistent results regarding the association of asbestos exposure with gastrointestinal cancers. Some studies reported slightly elevated death risks of gastrointestinal cancers in asbestos workers (Pira et al 2005;Hein et al 2007), but others did not (Doll and Peto 1985;Consensus Report 1997;de La Provote et al 2002). In the Quebec miner cohort, a substantial excess in mortality from gastrointestinal cancers was reported, but the authors found that exposure-response curves were far from regular, suggesting that some other factors, such as environmental, perhaps selective, might also operate (McDonald et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the small number of deaths and the weakness of the association, 2 -3 mis-diagnosed deaths would be enough to explain the elevated SMR. It should be noted, however, that data from literature do not fully agree on the association between the above cancers, mainly laryngeal, gastrointestinal and ovarian cancer and asbestos exposure (Doll and Peto, 1985;Zheng et al, 1992;Consensus Report, 1997;Rafferty et al, 2001;De la Provote et al, 2002;Griffiths and Malony, 2003).…”
Section: Discussionmentioning
confidence: 99%